2018
DOI: 10.1002/ab.21808
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and cyber bullying and sexual harassment: A longitudinal assessment of risk and protective factors

Abstract: Adolescents engage in bullying and sexual harassment perpetration both in-person and online. Yet, little is known about the overlap of traditional (in-person) and cyber bullying and sexual harassment perpetration. The present study assessed the co-occurrence of these forms of aggression in high school and identified middle school predictors based on participants' perceptions of factors across the social ecology. Racially diverse middle and high school students (n = 3549) were surveyed over four time points fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 53 publications
(74 reference statements)
3
33
0
3
Order By: Relevance
“…Furthermore, investigating how adolescents with moderate or high levels of antagonism use technologies would help prevent offensive and aggressive behaviors towards others. In fact, both the problematic use of technologies and hostility/aggression were predictors of direct and indirect violence in longitudinal studies (Gamez‐Guadix, Borrajo & Almendros, 2016; Leemis, Espelage, Basile, Mercer Kollar & Davis, 2019; Tang & Fox, 2016). This study has some limitations that should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, investigating how adolescents with moderate or high levels of antagonism use technologies would help prevent offensive and aggressive behaviors towards others. In fact, both the problematic use of technologies and hostility/aggression were predictors of direct and indirect violence in longitudinal studies (Gamez‐Guadix, Borrajo & Almendros, 2016; Leemis, Espelage, Basile, Mercer Kollar & Davis, 2019; Tang & Fox, 2016). This study has some limitations that should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, if children do not coordinate self‐ and peer evaluations, high self‐evaluation of showing respect may be associated with high aggression and low group‐level social competence. One limitation of the threatened ego hypotheses is that it focuses on measuring discrepancies (e.g., David & Kistner, ) rather than coordination among multiple evaluators, as has been the focus of many studies (Chang, ; Leemis, Espelage, Basile, Kollar, & Davis, ) or experimental manipulations (Sandstrom & Herlan, ). For example, in a recent longitudinal study Leemis and colleagues () found high self‐esteem and a sense of belonging increased the risk for traditional bullying in high school.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of the threatened ego hypotheses is that it focuses on measuring discrepancies (e.g., David & Kistner, ) rather than coordination among multiple evaluators, as has been the focus of many studies (Chang, ; Leemis, Espelage, Basile, Kollar, & Davis, ) or experimental manipulations (Sandstrom & Herlan, ). For example, in a recent longitudinal study Leemis and colleagues () found high self‐esteem and a sense of belonging increased the risk for traditional bullying in high school. A potential explanation they put forward is that bullies sometimes overestimate their peer acceptance and their high self‐esteem may lead to aggression if another person or a particular situation disagrees with their self‐esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Using a person‐centered approach is important to identify heterogeneity in response strategies and explore intraindividual variation in students' responses . To our knowledge, only 2 studies used a person‐centered approach to examine profiles of risk and protective factors among youth involved in bullying . However, this research did not focus on physical violence or bullying perpetration specifically among males, the population most likely to engage in these behaviors.…”
mentioning
confidence: 99%